Social networks in the improvement of learning in STEM areas in secondary education: Cambiando las percepciones del docente sobre el uso de las redes sociales - Álvarez-Herrero, Juan-Francisco (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The present demands the transformation of education with the introduction of new strategies and resources that guarantee a quality education. The use of social networks can report improvements in student learning. This research tries to find out the perceptions of STEM teachers regarding the use of social networks to improve learning. Carrying out effective training in the use of these networks in STEM education allows both the improvement of teachers' perceptions of these networks, and an increase in their use in their daily practices.